Incidence and profile of neurological disorders in alcohol dependents - Singh Baghel, Vijay; Shrivastava, Vasant (International Journal of Medical Research and Review, 2020)
Background: Alcohol is one of the most abused substances in the world. Alcohol has been known to produce toxic effects in almost every organ system in the body, many of these medical conditions can be attributed to the direct toxic effect of alcohol and its metabolites, whereas others are indirect sequelae that may result from nutritional deficiency particularly thiamine. A neurological complication of alcohol dependence is extremely common and affects every level of neuroaxis including the Brain-Peripheral nervous system-Muscle. Aim & Objective: To quantify the number of different neurological disorders in alcohol-dependent patients and to the established relationship between the frequency of these disorders with type, duration, amount, and frequency of alcohol intake. Method & Material: A cross-sectional study was conducted in 100 alcoholics who came to tertiary care centers of central India in the 1-year duration. Demographic data, questions related to their alcohol consumption, and Neurological examination of all patients were done as pre-decided protocol. Informed consent was obtained from all patients. Data was entered and analyzed using appropriate software. Result: Study participants were mostly (70%) in the age group of 21 to 40 years, 87% resided in the urban area, 81% were Hindu. 78% were educated up to class 8th and 76% were employed with any kind of jobs. There were 64% of cases that had any kind of neurological manifestation, 20% had peripheral neuropathy and less than 10% has severe manifestation Korsakoff’s psychosis, and cerebellar degeneration. Conclusion: Neurological manifestations were common among alcohol dependents, but it variably depends on the amount, pattern, chronicity, and type of alcohol consumption. There is a need for further studies that specifically point out alcohol-related nervous manifestations.